Modelo básico de gestión administrativa para mejorar la productividad de la vidriería “Niza” del cantón Latacunga en el período 2015 - 2016 - Casa Rodríguez, Miriam Elizabeth (2016)
The investigation was born from the need to implement in “Niza” Glassmaking a Basic Model of Administrate Management to improve its productivity, because there are administrative and operational needs. The purpose of this investigation is provide a management tool to the business owner to strengthen the work of the employees and workers in different areas that has. On the administrative side there are the strategic direction the administrative process and organizational structure as well as establishment of indicators that will permit to check the efficiency, efficacy and effectiveness of the model, there fore, that the operational part is strengthen with the description of each sequential processes to be carried out in the production area with their respective indicators that will permit to measure the productivity….